PENGARUH MODEL PEMBELAJARAN FLIPPED CLASSROOM BERBANTUAN VIDEO PEMBELAJARAN TERHADAP KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR IPA DI SMPN 27 SAMARINDA - Chipsy, Anggi Putri Yulia; Purwati, Sri; Herliani; Serena, Nelda A.; Masitah; Akhmad (PendIPA Journal of Science Education, 2025)
This study aims to determine the effect of the flipped classroom learning model assisted by instructional videos on the critical thinking skills and science learning outcomes of seventh-grade students at SMP Negeri 27 Samarinda. The research used a quasi-experimental method with a non-equivalent control group design. The sample consists of 21 students, with the experimental group using the flipped classroom model and the control group using the Student Team Achievement Division (STAD) model. The results show that in the experimental group, the average pretest and posttest scores for critical thinking increased from 28.29 to 76.67 (N-gain 0.67), and learning outcomes improved from 24.76 to 77.10 (N-gain 0.69). In contrast, in the control group, critical thinking scores increased from 20.29 to 64.29 (N-gain 0.54), and learning outcomes improved from 16.48 to 62 (N-gain 0.54). The t-test showed a significance value of 0.000 < 0.05, with t-value > t-table for both critical thinking and learning outcomes. In conclusion, the flipped classroom model assisted by instructional videos has a significant impact on enhancing students' critical thinking skills and science learning outcomes.